“Impacts of neo-banks on North African migrants’ remittances and financial inclusion” - Abdeslam Badre (Scientific African)
This study examined remittance trends and financial institution preferences among North African migrants in Europe and assessed neobanks' potential to foster financial inclusion and cost reductions. The main objetive was to explore how neobanks can alleviate economic pressures on North African migrants and help achieve the World Bank Group's goal of reducing remittance costs to 5 % and the UN-SDG target of 3 %. Exploratory in nature, both surveys and interviews were used for data collection. The sample consisted of 64 North African migrants from Morocco, Tunisia, and Algeria (North Africa) residing in France, Spain, and Italy (EU). Key findings revealed that North African migrants had diverse remittance behaviors, with varying frequencies and amounts sent home. Trust in traditional banks remained high due to familiarity, cultural norms, and accessibility issues in rural areas. However, neobanks offered significant cost savings, with potential annual savings ranging from €30 to €134 depending on the monthly remitted amount that ranges between a €100 and a €1000 . Adoption of neobanks was higher among younger, and digitally literate migrants with better access to technology. Barriers to wider adoption of neobanks included limited digital and financial literacy, lack of necessary technology in home countries, and cultural resistance to change. High regulatory and compliance costs for traditional banks also contributed to inflated remittance fees. To address these issues, the paper recommends enhancing market competition, improving access to new payment technologies, encouraging larger remittances through incentives, learning from successful public bank models like France's La Banque Postale, and fostering financial literacy and digital inclusion. Additionally, it suggests building trust and cultural sensitivity, investing in robust cybersecurity measures, and developing offline transaction capabilities to increase accessibility for migrants in remote areas.